Estudo da rede de informação legislativa e jurídica LexML Brasil sob o prisma da Arquitetura da Informação - PAIVA, Rodrigo Oliveira de (2017)
It studies the characteristics of the Legislative and Juridical Information Net Portal, so called LexML Brasil, according to the four basic beginnings of the Information Architecture for the web, proposed by Louis Rosenfeld and Peter Morville (1998), they are: organization system, navigation system, tagging system and search system, besides additional elements proposed by Straioto (2002): content of the information, usability and types of documents. The work has as general objective to study the characteristics of LexML Brasil Portal starting from the elements of the Information Architecture. As specific objectives to identify and to describe the characteristics of LexML Brazil Portal starting from the elements of the Information Architecture. With relationship to the nature and in agreement with the proposed objectives the methodological character of that work corresponds to a qualitative and explanatory-descriptive research. The approach method used it was the hypothetical-deductive and the operational method was the monographic. For the literature review, the research was accomplished in books, newspapers, dissertations, theses and scientific articles already published approaching the thematic. The analysis of the results identified that the architecture of the portal presents all the systems of the Information Architecture studied, in bigger or in smaller amount, however always presenting some element type. By the presented results, it was ended that the need of application of beginnings of Information Architecture for web in Legislative and Juridical Information Net Portal - LexML Brasil is of fundamental importance to enlarge and to facilitate the access to the information for the public user of the referred net.